1982
DOI: 10.1093/infdis/146.5.616
|View full text |Cite
|
Sign up to set email alerts
|

Entamoeba histolytica Cytotoxin: Purification, Characterization, Strain Virulence, and Protease Activity

Abstract: A heat-labile cytotoxin was isolated from virulent strains of axenically cultivated Entamoeba histolytica. Strains of E. histolytica representing a spectrum of virulence as determined in animal and in vitro models of disease were examined for cytotoxic activity. Extracts of virulent strain HM1 possessed marked cytotoxic activity, those of moderately virulent strain 200 showed intermediate activity, and those of avirulent strains 303 and Rahman showed no activity. The cytotoxin was partially purified from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…In contrast to the marked inhibitory effect on the phagocytosis induced by HM1:IMSS toxin, the toxin of the less virulent strain NIH:200 did not produce a significant inhibitory effect on the activity of PMNs. This is in agreement with the report by McGowan et al [12] who demonstrated that strain HM1:IMSS possessed marked cytotoxic activity on PMNs while strain NIH:200 exhibited a moderate activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast to the marked inhibitory effect on the phagocytosis induced by HM1:IMSS toxin, the toxin of the less virulent strain NIH:200 did not produce a significant inhibitory effect on the activity of PMNs. This is in agreement with the report by McGowan et al [12] who demonstrated that strain HM1:IMSS possessed marked cytotoxic activity on PMNs while strain NIH:200 exhibited a moderate activity.…”
Section: Discussionsupporting
confidence: 93%
“…histolytica toxin (Ehp/t) was obtained from the virulent strain HM1:IMSS was kindly provided by Dr. Pittman (USA). Toxin of strain NIH:200 was prepared from axenic trophozoites as described by McGowan et al [12].…”
Section: Entamoeba Histolytica Toxinmentioning
confidence: 99%
“…The analysis revealed that we could successfully differentiate the genotypes of E. histolytica and E. dispar. Additionally, strain EH (Rahman), a less virulent strain as assessed by decreased monolayer destruction, disease in animal models, cytotoxicity, and the only EH strain isolated from an asymptomatic individual was the most divergent of the EH strains and clustered separately from the virulent EH strains with significant bootstrap values (13,27,(48)(49)(50)(51). The separation of the EH (Rahman) strain from the other EH strains could also reflect the geographic origins of the strains and be unrelated to parasite phenotypes.…”
Section: Vol 4 2005 Genotypes Of Entamoeba Correlate With Virulencementioning
confidence: 99%
“…Interstrain variations in the adhesion of E. histolytica trophozoites to human epithelium have been demonstrated for two E. histolytica strains (1,10), in which underrepresentation of the 35-kDa light subunit of the Gal-GalNAc lectin in the avirulent Rahman strain was shown to be correlated with a lack of cytopathic activity (1). Variations in cysteine proteinase expression between highly virulent and avirulent strains were also reported (23). In addition, marked differences in the levels of lipophosphoglycan-like and lipophosphopeptidoglycan molecules were demonstrated between virulent and avirulent strains of E. histolytica (24).…”
mentioning
confidence: 93%